Sun exposure and multiple sclerosis risk in Norway and Italy: The EnvIMS study. (July 2014) - Bjørnevik, Kjetil; Riise, Trond; Casetta, Ilaria; Drulovic, Jelena; Granieri, Enrico; Holmøy, Trygve; Kampman, Margitta T; Landtblom, Anne-Marie; Lauer, Klaus; Lossius, Andreas; Magalhaes, Sandra; Myhr, Kjell-Morten; et al.
Objectives: The objective of this paper is to estimate the association between multiple sclerosis (MS) and measures of sun exposure in specific age periods in Norway and Italy. Methods: A total of 1660 MS patients and 3050 controls from Italy and Norway who participated in a multinational case-control study (EnvIMS) reported sun habits during childhood and adolescence. Results: A significant association between infrequent summer outdoor activity and increased MS risk was found in Norway and in Italy. The association was strongest between the ages of 16 and 18 years in Norway (odds ratio (OR) 1.83, 95% confidence interval (CI) 1.30–2.59), and between birth and age 5 years in Italy (OR 1.56, 95% CI 1.16–2.10). In Italy a significant association was also found during winter (OR 1.42, 95% CI 1.03–1.97). Frequent sunscreen use between birth and the age of 6 years was associated with MS in Norway (OR 1.44, 95% CI 1.08–1.93) after adjusting for outdoor activity during the same period. Red hair (OR 1.67, 95% CI 1.06–2.63) and blonde hair (OR 1.36, 95% CI 1.09–1.70) were associated with MS after adjusting for outdoor activity and sunscreen use. Conclusion: Converging evidence from different measures underlines the beneficial effect of sun exposure on MS risk.